Pesticides in insectivorous birds: a quantitative analysis of the contamination outlook (Research, Society and Development, 2020)
The main pesticides used are insecticides, herbicides and fungicides. From these substrates, wild fauna is exposed to these pollutants. However, birds show greater degrees of sensitivity, when compared to other vertebrates, the exposure of various compounds used in agriculture. Thus, through a scientometric approach, the objective of the present study was to verify and characterize the development of the worldwide scientific knowledge about the contamination of insectivorous birds by pesticides. In the search conducted with a focus on publications that investigated pesticides in insectivorous birds a total of 155 articles were identified for the period from 2014 to 2108. After the thorough selection process of the articles, we obtained only 6 articles that carried out studies of contamination in birds insectivores through some type of pesticide. These studies studied 52 species of birds where 23 of these species showed a population trend classified as decreasing (DE). The results showed that they had at least one organ / tissue / structure (stomach bolus, blood plasma, muscle tissue, food items,) contaminated by one of the 29 types of chemical compounds found in the analyzed articles. Although it has been found that there is a global theoretical gap in relation to ecotoxicological research, demonstrating the impact of pesticides on the environment, studies with insectivorous birds have shown to be excellent mechanisms for environmental monitoring in the face of changes occurring in ecosystems, resulting from production and can provide relevant information for decision-making and the establishment of public policies in Brazil and worldwide.